Cardiospermum halicacabum derived MoO3 nanoparticles for Fluorescence sensing, DNA binding and Cytotoxicity Studies - Sanniyasi Rajeswari; Seth Sheeba Thavamani (The Bioscan, 2025)
MoO3 nanoparticles were biosynthesised using Cardiospermum halicacabum leaf extract. Their structural and morphological properties were investigated through UV–visible DRS studies, photoluminescence, Fourier Transform Infra-Red spectroscopy, Energy-Dispersive X-ray analysis, X-Ray Diffraction, X-Ray Photoelectron Spectroscopy and High-Resolution Transmission Electron Microscopy. O2-→Mo6+ transition was confirmed by the peak observed at 353nm in UV-Visible spectrum and the band gap was estimated as 2.48 eV. Mo-O-Mo bond was confirmed by the bands observed at 842 cm-1 and 475 cm-1 in FTIR spectroscopy. EDX spectra showed characteristic peaks of oxygen and molybdenum. XPS showed binding energies of 232.4 and 235.6 eV, which correspond to spin-orbit splitting of Mo 3d5/2 and Mo 3d3/2 respectively, which confirmed that Mo is present in +6 state. The particle size was determined to be 69 nm using XRD analysis. Effective fluorescence sensing of Pb2+ was observed with a detection limit 4.13x10-8 M. ct-DNA binding constant was calculated as 3.09 (mg/mL)-1 and 2.32 (mg/mL)⁻¹ using UV-Vis and fluorescence studies respectively. Cytotoxicity studies using A549 Human Lung cancer cell line showed IC50 value of 249.5 μg/mL